أثر برنامج تدريبي مقترح قائم على المعايير المهنية للمعلمين في تنمية الأداء التدريسي لدى معلمات العلوم بالمرحلة المتوسطة - الشهراني، أمل بنت عبدالله علي (جامعة الملك سعود - الجمعية السعودية للعلوم التربوية والنفسية - جستن, 2022)
هدف البحث إلى تعرف أثر برنامج تدريبي مقترح قائم على المعايير المهنية للمعلمين في تنمية الأداء التدريسي لدى معلمات العلوم بالمرحلة المتوسطة، واعتمد البحث المنهج التجريبي ذا التصميم شبه التجريبي، وتم بناء برنامج تدريبي مقترح قائم على المعايير المهنية للمعلمين، وإعداد مقياس للأداء التدريسي لمعلمات العلوم، وتكونت عينة البحث من (22) معلمة من معلمات العلوم بالمرحلة المتوسطة بمدينة أبها تم تدريبهن وتطبيق مقياس الأداء التدريسي عليهن قبليا وبعديا. وقد أسفرت النتائج عن وجود فروق دالة إحصائيا عند مستوى الدلالة (0.05) بين متوسطات درجات معلمات العلوم في التطبيقين القبلي والبعدي لمقياس الأداء التدريسي لصالح التطبيق البعدي. The research aimed at identifying the impact of a teacher professional standard-based proposed training program on the teaching performance development of female science teachers at middle school. It adopted the Quasi-experimental design of the empirical method. A teacher professional standard-based proposed training program was developed, and the teaching performance measurement of the female science teachers was prepared. The research sample consisted of (22) female science teachers at the middle school in Abha, who were trained and upon whom the prior and posterior teaching performance measurement was applied. The findings of the research showed statistical differences at the level of statistical significance of (0.05) between the average degrees achieved by the female science teachers in the prior and posterior application of the teaching performance measurement towards the post-application.
Keywords: المعايير المهنية -- الأداء الوظيفي -- التدريب المهني -- الموارد البشرية -- السعودية